Post-operative complications: Análisis de los factores de riesgos (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2021)
The postoperative complication is a serious problem, difficult for the surgeon. Poor prognostic factors (risk factors) are: age over 65 years, number of surgeries (more than two), generalized peritonitis, malnutrition, shock, and multiple organ failure.Severity indices (prognostic factors) allow quantifying and predicting the risk of morbidity and mortality according to analytical or clinical physiological parameters, their application is a valid and rigorous way to measure the probability of complications and postoperative mortality.The objective is to determine prognostic factors (risk factors) for mortality in patients with postoperative complications.Results.- In order to determine morbidity and mortality, a retrospective and observational study was carried out with 184 patients who underwent surgery in the surgery service of the Dr. Abel Gilbert Pontón hospital. Of the 184 records reviewed, 62 patients (34%) required reoperation. The general mortality of the cases was 15% and that of the reoperated cases 9.7%.
Keywords: Risk factors; postoperative complications.